A multifactorial investigation of captive gorillas' intraspecific gestural laterality. Issue 5 (3rd September 2018) - Prieur, Jacques; Pika, Simone; Barbu, Stéphanie; Blois-Heulin, Catherine
ABSTRACT: Multifactorial investigations of intraspecific laterality of primates' gestural communication aim to shed light on factors that underlie the evolutionary origins of human handedness and language. This study assesses gorillas' intraspecific gestural laterality considering the effect of various factors related to gestural characteristics, interactional context and sociodemographic characteristics of signaller and recipient. Our question was: which factors influence gorillas' gestural laterality? We studied laterality in three captive groups of gorillas ( N = 35) focusing on their most frequent gesture types ( N = 16). We show that signallers used predominantly their hand ipsilateral to the recipient for tactile and visual gestures, whatever the emotional context, gesture duration, recipient's sex or the kin relationship between both interactants, and whether or not a communication tool was used. Signallers' contralateral hand was not preferentially used in any situation. Signallers' right-hand use was more pronounced in negative contexts, in short gestures, when signallers were females and its use increased with age. Our findings showed that gorillas' gestural laterality could be influenced by different types of social pressures thus supporting the theory of the evolution of laterality at the population level. Our study also evidenced that some particular gesture categories are better markers than others of the left-hemisphere language specialization.